PENGARUH PROFITABILITY, WORKING CAPIRAL, DAN FREE CASH FLOW TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Junior, Richard; Bangun, Nurainun (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The main purpose doing this study is to analyze the effect of Profitability, Working Capital, and Free Cash Flow of Financial Distress on manufacturing companies listed in the Indonesian Stock Exchange in period 2018-2020. In this research used E-views 12 and Microsoft Excel 2019 for processing data. This research used the Purposive Sampling for the sample selection, based in the kriteria in this research there is 71 manufacturing companies in used in this research and the total is 213 sample for 3 years. In this research the result is Profitability have a positive and significant effect on Financial Distress, Working Capital have a positive and significant on Financial Distress, and Free Cash Flow have negative and not significant on Financial Distress.